Optimization and Comparison of Microwave‐Assisted Extraction, Supercritical Fluid Extraction, and Eucalyptus Oil–Assisted Extraction of Polycyclic Aromatic Hydrocarbons from Soil and Sediment. (10th April 2023) - Kariyawasam, Thiloka; Doran, Gregory S.; Howitt, Julia A.; Prenzler, Paul D.
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are persistent organic compounds of major concern that mainly accumulate in soils and sediments, and their extraction from environmental matrices remains a crucial step when determining the extent of contamination in soils and sediments. The objective of the present study was to compare the extraction of PAHs (phenanthrene, pyrene, chrysene, and benzo[ a ]pyrene) from spiked soil and sediment using supercritical fluid extraction (SFE) with ethanol as the modifier, microwave‐assisted extraction (MAE), and eucalyptus oil–assisted extraction (EuAE). Recoveries of PAHs were comparable between the three methods, and >80% of applied pyrene, chrysene and benzo[ a ]pyrene were recovered. The most efficient method of extracting PAHs from naturally incurred soils with different levels of contamination was SFE. A longer extraction time was required for the EuAE method compared with SFE and MAE under optimized conditions. However, EuAE required lower extraction temperatures (15–20 °C) compared with SFE (80 °C) and MAE (110–120 °C), and consumed less solvent than SFE and MAE. Compared with hexane/acetone used in MAE, the use of ethanol in SFE and eucalyptus oil in EuAE can be considered as more sustainable approaches to efficiently extract PAHs from spiked/naturally contaminated soils and sediments. And, although less efficient for matrices containing higher carbon content, EuAE offered a cheap, low‐tech approach to extracting PAHs. Environ Toxicol Chem 2023;42:982–994. © 2023 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.